Evaluation of Quality of Life in Dogs with Idiopathic Epilepsy. (24th February 2014) - Wessmann, A.; Volk, H.A.; Parkin, T.; Ortega, M.; Anderson, T.J.
<x xml:space="preserve">Abstract</x> Background The impact of epilepsy and its treatment on the quality of life (QoL) is considered an important part of treatment supervision in human epilepsy. Objectives To develop a list of key questions evaluating QoL in dogs with idiopathic epilepsy (IE) and their carers. Animals One hundred fifty‐nine dogs with IE. Methods Cross‐sectional study. An online project questionnaire was developed containing 90 QoL‐associated questions that were initially allocated to 14 themes representing specific areas associated with the treatment and care of an epileptic dog. Principal component analysis was applied with the aim of refining the questionnaire to the least number of questions representing useful themes without loss of descriptive value. Carers were recruited by paper mail, primary practices, and canine epilepsy websites. Data were acquired from January to November 2011. Results Principal component analysis removed 54 questions, leaving 7 themes with 36 questions with a minimum Cronbach's alpha value of 0.7 indicating a good internal consistency: "Seizure severity and frequency", "Adverse effects of antiepileptic drug (AED)", "Restrictions on the carer's life", "Frustrations over caring for a dog with IE", "Carer distaste of AED adverse effects", "Carer anxiety around the seizure event", "Perceptions on rectal diazepam use". Conclusions and Clinical Importance Principal component analysis successfully reduced the number of questions without loss in descriptive value. The remaining questions correlate well with each other in capturing valuable details about aspects of QoL and represent valuable key questions (EpiQoL) in the assessment of QoL for the carers of dogs with IE.